La genética molecular de bovinos y equinos criollos en los albores del siglo XXI - Giovambattista, Guillermo (2010)
American Creole bovines and equines are direct descendant from the animals introduced by European conquerors during XV an XVI centuries. At the beginning of the last decade, new technologies based in DNA emerged for genetic analysis, and Creole breeds were not the exception for these kind of studies. During the last years, these methodologies evolved vertiginously. In a short time, the amount of available information increased, and the analysis of few loci turned into analysis of complete genomes. This work describes the evolution of Creole, cattle and equines, molecular genetic studies during the last fifteen years. Even though, Creole breeds have not entered yet into genomic and proteomic era, its study is relevant because they are suffering a progressive population reduction. In this sense, information about infectious diseases resistance, adaptability, forensic genetics, animal production and phylogeography, among others, can be obtained from them. Furthermore, Creole breeds are a unique natural reservoir of genetic variability, and strategies for its conservation should be implemented.